Innovative Behavior And Emotional Intelligence Of Managers In Managing A Catering Business - Salma Abdullah, La Ode Sumail, (Jurnal Manajemen, 2019)
The main problem of SME Catering family business in Makassar City is low competitiveness which has an impact on financial performance. This study investigates the causes of low competitiveness through the role of the manager's innovative behavior and emotional intelligence. Sampling uses purposive sampling by setting the owner and manager as respondents. Data was transformed from the score to scale data through SolAnd 1.9 software application and data analysis using WarpPLS 3.0. This study found that Catering's financial performance is good because ownership is increasing. The more catering ownerships are the better innovation of managers and better financial performance. Although innovative managers are good, the emotional intelligence of managers is still low, financial performance is also low. The catering business is vulnerable to the risk of raw materials. Therefore, managers who are able to innovate and have personal qualities to work are needed indeed the competitiveness of this business increases.